Perlindungan Hukum Terhadap Hak Kekayaan Intelektual Hak Cipta dalam Perspektif Hukum Pidana - Yusdinsyah, Dwi Anugrah (Proceedings Series on Social Sciences & Humanities, 2024)
Indonesia is a country of law, not a country of power. This declaration is clearly explained in Article 1 paragraph (3) of the 1945 Constitution. As a constitutional state, Indonesia has a number of legal provisions. One of the provisions of this law is copyright law. Meanwhile, copyright actually falls within the scope of the Intellectual Property Rights (IPR) Law. This research uses many approaches, including a legal approach which is carried out by examining all legal provisions relating to the legal issues being studied. Apart from that, the conceptual approach also deviates from the perspectives and theories developed in legal science. One of the common obstacles is weak law enforcement against copyright infringement. This is caused by various factors, including a lack of human resources, technology and budget for copyright enforcement. In addition, courts continue to face obstacles in handling copyright infringement cases, including judges' limited knowledge of copyright and a lack of evidence. It can be concluded that copyright law enforcement in Indonesia still faces several problems, such as weak supervision and inefficient law enforcement. This has an impact on the number of piracy cases that occur in Indonesia. To increase the application of criminal sanctions for copyright infringement, the Indonesian government needs to strengthen law enforcement and provide education and training to judges and other judicial personnel.